2021
DOI: 10.1002/adom.202002007
|View full text |Cite
|
Sign up to set email alerts
|

All‐Dielectric Metasurface for Manipulating the Superpositions of Orbital Angular Momentum via Spin‐Decoupling

Abstract: Vortex beam has attracted much attention for carrying orbital angular momentum (OAM). It has a helical phase structure described by exp (ilθ) and an annular intensity distribution, where l is the topological charge corresponding to the OAM of each photon, and θ is the azimuth angle. [1] Vortex beam is widely used in OAM communications, [2,3] optical tweezers, [4] and quantum information coding. [5,6] In particular, the superposition of OAM states is very significant in metrology, [7,8] quantum science, [6,9] a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 54 publications
0
31
0
Order By: Relevance
“…This novel method greatly expands the application scope of metasurface polarization optics and paves an innovative way to generate high-efficiency, multichannel, and multidimensional FOVs and vector vortex beams. Using a kind of dielectric metasurface composed of staggered arrangements of anisotropic and isotropic meta-atoms, Zheng et al experimentally demonstrated polarization-controllable superpositions of OAM states in the terahertz band by combining the propagation phase and PB phase [40]. Xu et al produced two types of polarization-dependent metasurfaces and successfully presented the terahertz cylinder vector beam and vector Bessel beam [41].…”
Section: Introductionmentioning
confidence: 99%
“…This novel method greatly expands the application scope of metasurface polarization optics and paves an innovative way to generate high-efficiency, multichannel, and multidimensional FOVs and vector vortex beams. Using a kind of dielectric metasurface composed of staggered arrangements of anisotropic and isotropic meta-atoms, Zheng et al experimentally demonstrated polarization-controllable superpositions of OAM states in the terahertz band by combining the propagation phase and PB phase [40]. Xu et al produced two types of polarization-dependent metasurfaces and successfully presented the terahertz cylinder vector beam and vector Bessel beam [41].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with conventional optical devices dependent on phase accumulation, metasurfaces can obtain abrupt phase change within subwavelength thickness by appropriately changing specific parameters, thereby generating various functions [4,5] . Specifically, metasurfaces can generate spatial phase discontinuities over the entire 2π range of a specific frequency, which have manifested that they can be utilized in a flat wave plate [6,7] , hologram imaging [8][9][10] , beam deflectors [11,12] , achromatic focusing lenses [13,14] , spin-orbital angular momentum manipulation [15][16][17][18] , and other fields.…”
Section: Introductionmentioning
confidence: 99%
“…However, the output waves of PB phase metasurfaces under orthogonal CP waves have inherent correlation. To break this restriction, spin-decoupled metasurfaces combining PB phase with dynamic phase were designed to independently manipulate the output waves under left-handed CP (LCP) and right-handed CP (RCP) incidences [12,18,21,22] . Spin-decoupled metasurfaces have many applications in holography [21] , focusing [18] , and polarization multiplexing [22] .…”
Section: Introductionmentioning
confidence: 99%
“…and high-refractive-index dielectric materials have been recently developed to replace plasmonic metasurfaces to remove conductor loss. [27][28][29][30][31][32][33][34][35][36][37] Various optical dielectric metasurface devices have been demonstrated, such as metalenses, [27,28] beam splitters, [29][30][31] polarization converters, [32][33][34] and vortex beam generators. [35][36][37] However, limited progress has been achieved in dielectric metasurfaces in the THz band due to the challenging fabrication processes.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29][30][31][32][33][34][35][36][37] Various optical dielectric metasurface devices have been demonstrated, such as metalenses, [27,28] beam splitters, [29][30][31] polarization converters, [32][33][34] and vortex beam generators. [35][36][37] However, limited progress has been achieved in dielectric metasurfaces in the THz band due to the challenging fabrication processes. Conventional integrated circuits lithography and reactive ion etching (RIE) technologies are typically applied to process thin films a few micrometers thick.…”
Section: Introductionmentioning
confidence: 99%